2014
DOI: 10.11646/phytotaxa.159.4.3
|View full text |Cite
|
Sign up to set email alerts
|

A new endemic Ramalina species from the Canary Islands (Ascomycota, Lecanorales)

Abstract: Ramalina alisiosae (Ramalinaceae), found on trees in the laurel forests of the Canary Islands is described as new to science. A description of the species is given together with notes on its chemistry, distribution, ecology, and taxonomy. Bayesian and Maximum Likelihood analyses of ITS sequences showed a close relation of the new species with R. implectens and R. farinacea. Morphological and anatomical differences with these related lichen taxa are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…As in previous studies (e.g. Pérez-Vargas & Pérez-Ortega 2014; Gasparyan et al . 2017; references therein), the relationships among many of the Ramalina taxa included in our broader phylogeny remain unresolved (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As in previous studies (e.g. Pérez-Vargas & Pérez-Ortega 2014; Gasparyan et al . 2017; references therein), the relationships among many of the Ramalina taxa included in our broader phylogeny remain unresolved (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…2010; Timsina et al . 2012; Pérez-Vargas & Pérez-Ortega 2014; Gasparyan et al . 2017), and of species complexes within Ramalina (Groner & LaGreca 1997; LaGreca 1999; Ohmura et al .…”
Section: Introductionmentioning
confidence: 99%
“…To establish whether a record is new for La Palma or the Canary Islands, the most recent checklist for lichens and lichenicolous fungi of the Canary Islands, Hernández-Padrón & Pérez-Vargas (2010), was consulted and indicated as H-2010 below. The following more recent publications were also checked: Aptroot & Schumm (2012), van den Boom (2010Boom ( , 2013, van den , van den Boom & Ertz (2012), van den Boom & Etayo (2017), van den , Giralt & van den Boom (2011), Montelongo et al (2015), Pérez-Vargas & Pérez-Ortega (2014), Pérez-Vargas et al (2010b, 2010d, 2012a, 2012b, 2015a, 2015b and Tehler et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…Culberson 1967;Sheard & James 1976;Rundel 1978;Krog & Østhagen 1980;Stevens 1987). However, recent studies have shown that different morphological and/or chemical characteristics, once thought to be caused by environmental factors, can also indicate distinct species (Kashiwadani et al 2007;Ohmura et al 2008;Hayward et al 2014;Pérez-Vargas & Pérez-Ortega 2014).…”
Section: Introductionmentioning
confidence: 99%